HUBUNGAN PEKERJAAN DAN PENDIDIKAN DENGAN PERKEMBANGAN BAHASA PADA ANAK USIA TODDLER DI WILAYAH KERJA PUSKESMAS LUBUK BUAYA PADANG TAHUN 2018 - Komalasari, Wuri (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Late language delay in the early period, can cause various problems in the learning process at school age. Children who experience speech and language delays are at risk of learning difficulties, reading and writing difficulties, communicating with others, leading to underachieving academic achievement, this can continue until young adulthood. Language delay in toddler can be caused by family characteristics such as, father / mother education and employment. This study aims to determine the employment and education with language development in Toddler in work area Puskesmas Lubuk Buaya Padang 2018. This research type was analytical with cross sectional design. The population in this study was 58 mothers who have children aged toddler in RW 1 and 2 Rimbo Jariang Lubuk Buaya Padang, the study was conducted on July 6 until July 9, 2018. This study used total sampling with a questionnaire research instrument. Data analysis was done in univariate analysis and bivariate analysis using chi-square test in computer. The result of this research shows that there is no correlation between employment with language development ( p value 1,000> 0,05) and there is no correlation between education with language development ( p value 0,472> 0,05). It is recommended for the Puskesmas to provide counseling for mothers about how to stimulate children so that their development is appropriate for age. Literature : 27 (2009-2017) Keywords: Toddler, Employment, Education, Language Development.